Pemanfaatan Tepung Tulang Ikan Patin dengan Penambahan Kacang Tunggak sebagai Sumber Kalsium pada Pembuatan Snack Bar - Nadhilah Syarafina; Dudung Angkasa; Reza Fadhilla; Prita Dhyani Swamilaksita (Jurnal Pangan dan Gizi, 2022)
Fish bone, as a food waste, and cowpea can be a high potential ingredient to develop a healthy snack food. This study aimed to compare and sensory properties of a snack food made from ratio of fish bone and cowpea. This experimental study manipulate fish bone (FB) and cowpea (CW) waste into four formula F0 (control), F1 (90g:20g), F2 (80g:30g). ) and F3 (70g:40g). Proximate and calcium analysis was carried out in an accredited laboratory, while the sensory analysis was evaluated by semi-trained and consumer panelists. One Way-Anova test with Post Hoc test was performedto answer research question. There is significant difference among all formulas (p<0.05) in the parameters of color, aroma, texture and taste. The snack bar F3 was the most preferred by the panelists. This formulation contains 12.06% protein and 5572 mg calcium and can be claimed as a calcium source snack. The greater the concentration of patin bone meal, the higher the calcium content of the snack bar. The hedonic test showed that increase in the concentration of patinbone meal had an effect on the texture, aroma and taste of the resulting snack bar.